Mechanochemical synthesis of tetrahedrite materials using mixtures of synthetic and ore samples collected in the Portuguese zone of the Iberian Pyrite Belt. (1st April 2021) - Neves, F.; Esperto, L.; Figueira, I.; Mascarenhas, J.; Salgueiro, R.; Silva, T.P.; Correia, J.B.; Carvalho, P.A.; de Oliveira, D.
Highlights: Direct use of tetrahedrite-tennantite ore for processing of tetrahedrite-based materials was evaluated. The tetrahedrite-tennantite ore was collected in two different deposits located at the Iberian Pyrite Belt. Ore and multiphase synthetic samples were mixed in different mass ratios and processed via mechanochemical synthesis. Tetrahedrite-tennantite-(Fe) was the only sulfide phase identified in the mixtures with higher amounts of Barrigão dump ore. Tetrahedrite-tennantite-(Fe) coexisted with famatinite-luzonite and pyrite in mixtures with Neves Corvo ore. Abstract: Considering that the synthesis of tetrahedrite-based materials usually uses high purity elements, the evaluation of the direct application of ore samples as raw materials for their synthesis is a pertinent issue. In the present study, multiphase synthetic tetrahedrite samples were mixed with tetrahedrite-tennantite ore samples (in weight ratios of 0.8/0.2, 0.5/0.5 and 0.2/0.8) to produce tetrahedrite-based materials by solid-state mechanochemical synthesis. The ore samples were obtained from the abandoned Barrigão mine dumps and from the Neves Corvo mine, both located in the Portuguese zone of the Iberian Pyrite Belt, whose main constituents were found to be As-rich tetrahedrite and tennantite-(Fe), respectively. Depending on the ore sample and on the mixture ratios, the displacement reactions occurring during the synthesis process gave rise to different phase transformation paths. For the ratios of 0.5/0.5 and 0.2/0.8, the mixtures with the Barrigão ore were found to consist of a single sulfide phase, tetrahedrite-tennantite-(Fe), plus quartz, while famatinite was also observed in the 0.8/0.2 mixture. Tetrahedrite-tennantite-(Fe) phase was the main constituent of all mixtures with the Neves Corvo ore, but in all of them other sulfide phases, famatinite-luzonite and pyrite, were also present in addition to quartz. Despite being dissimilar, these results are very promising and encouraging, by confirming the possible direct usage of ore samples and of dump material for the synthesis of tetrahedrite-based materials with all the potential environmental-economic gains that can be obtained.